Cognitive linguistics - Croft, William (Cambridge University Press, 2004)
Cognitive Linguistics argues that language is governed by general cognitive principles, rather than by a special-purpose language module. This introductory textbook surveys the field of cognitive linguistics, presenting its theoretical foundations and the arguments supporting it. Clearly organised and accessibly written, it provides a useful introduction to this fast-growing area.
Keywords: Cognitive grammar.; Grammaire cognitive.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax.; Cognitive grammar; Kognitive Semantik; Metapher; Polysemie; Kognitive Linguistik; Semantik; Cognitieve linguïstiek.; Lingüística cognitiva.; Electronic book.